Ecdysterols and triterpene glycoside from Achyranthes aspera L. and their NO production inhibitory activity - Lan, Hoang Thi Tuyet; Mai, Nguyen Thi; Anh, Bui Thi Mai; Dung, Duong Thi; Huu Tai, Bui; Van Kiem, Phan (Vietnam Journal of Science and Technology, 2024)
Phytochemical study on the methanolic extract of the aerial parts of Achyranthes aspera led to the isolation of six compounds including five ecdysterols, makisterone A (1), achyranthesterone A (2), 24(28)-dehydromakisterone A (3), podecdysone C (4), 20-hydroxyecdysone (5), and 3-O-α-L-rhamnopyranosyl-(1→3)-β-D-glucuronopyranosyl-oleanolic acid 28-O-β-D-glucopyranosyl ester (6). Compounds 1-5 were first isolated from A. aspera. Their chemical structures were identified by 1D and 1D NMR spectra in comparison with the published data in literature. Al five ecdysterol significantly showed NO production inhibition effects in LPS-activated RAW264.7 cells with the IC50 values ranging from 27.21 to 40.47 µM compared to that of positive control compound, L-NMMA, 32.24 µM.